2020
DOI: 10.1093/mnras/staa788
|View full text |Cite
|
Sign up to set email alerts
|

Searching for solar siblings in APOGEE and Gaia DR2 with N-body simulations

Abstract: We make use of APOGEE and Gaia data to identify stars that are consistent with being born in the same star cluster as the Sun. We limit our analysis to stars that match solar abundances within their uncertainties, as they could have formed from the same Giant Molecular Cloud (GMC) as the Sun. We constrain the range of orbital actions that solar siblings can have with a suite of simulations of solar birth clusters evolved in static and time-dependent tidal fields. In the static tidal field, which contains a bul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 91 publications
2
4
0
Order By: Relevance
“…From our model fit, 95% of these stars should currently have 550 kpc km s −1 L z 2770 kpc km s −1 and J R 130 kpc km s −1 . This is roughly consistent with the results of Webb et al (2020), who used simulations to investigate the present-day positions of solar siblings in the (L z , J R , J z ) space in different possible potentials and constrained present-day solar siblings' angular momenta to 353 kpc km s −1 L z 2110 kpc km s −1 and J R 116 kpc km s −1 . The exact values of these bounds should depend on the detailed history of the Milky Way disk, but their model gives an angular momentum range of about 2000 kpc km s −1 , which is close to our 2σ(τ) value.…”
Section: Application To the Solar Siblings' Orbit Distributionssupporting
confidence: 89%
See 1 more Smart Citation
“…From our model fit, 95% of these stars should currently have 550 kpc km s −1 L z 2770 kpc km s −1 and J R 130 kpc km s −1 . This is roughly consistent with the results of Webb et al (2020), who used simulations to investigate the present-day positions of solar siblings in the (L z , J R , J z ) space in different possible potentials and constrained present-day solar siblings' angular momenta to 353 kpc km s −1 L z 2110 kpc km s −1 and J R 116 kpc km s −1 . The exact values of these bounds should depend on the detailed history of the Milky Way disk, but their model gives an angular momentum range of about 2000 kpc km s −1 , which is close to our 2σ(τ) value.…”
Section: Application To the Solar Siblings' Orbit Distributionssupporting
confidence: 89%
“…Therefore, the Sun could well have been born in a (possibly now fully disrupted) birth cluster that is different from the usual candidate cluster M67, which is known to have a similar age and metallicity to those of the Sun (Yadav et al 2008;Heiter et al 2014). Recent work has shown that M67 is unlikely to be the Sun's birth cluster, but this is not fully ruled out (Jørgensen & Church 2020;Webb et al 2020). Instead, the Sun's birth cluster could have formed at the same radius and time, but at a distinct azimuth from M67.…”
Section: Application To the Solar Siblings' Orbit Distributionsmentioning
confidence: 98%
“…If such a cluster initially had ∼ 10 4 members (Hurley et al 2005), this would be consistent with constraints from the Solar System properties (Portegies Zwart 2009;Adams 2010;Pfalzner 2013;Moore et al 2020). However, this scenario remains a subject of debate (Jørgensen & Church 2020;Webb et al 2020).…”
Section: Ramifications For the Solar Systemsupporting
confidence: 58%
“…Both options are not without difficulties. The overdensities arising from phase space clustering at birth may disperse on sub-Gyr timescales (Krumholz et al 2019;Webb et al 2020), much shorter than the ages considered here. This problem could be alleviated by the prediction that the destabilising effects of encounters persist well after a planetary system has escaped the birth environment (e.g.…”
Section: Individual Scenarios For Explaining the Radius Valleymentioning
confidence: 75%